Features of perception of religion in Japan (Journal of history, 2017)
There are different religions in various countries. In a same country, depending on the nationality and family can practice different religions. There are people who profess several religions at the same time. However, if in most countries it is considered a rarity, in Japan it is considered ordinary. According to many statistical studies in Japan, many people profess both Shinto and Buddhism. And if you exclude the Japanese profess one religion, there are not many people who can give a clear answer to the question of what religion they professe. Undoubtedly, from the history of Japan, we can understand that Shinto and Buddhism have been in close relationships for a long time. And how the Japanese manage to com- bine two different religions? According to one of the statistics, the percentage of believers in Japan is 24%, looking at what can be said that the remaining 76% – do not believe. Accoeding to one study, religion is not important for Japanese. This may be due to the fact that the Japanese have a completely different image to religion. This paper describes the results of the survey between the Japanese that the author had, in order to clarify the questions above.